36 Evaluating the effect of lower limb botulinum toxin a injections on goal-directed outcomes in ambulant children and young people with cerebral palsy. (23rd February 2023) - Katchburian, Lesley; Hodgson, Xanthe; Crowe, Belinda; Carr, Lucinda; Main, Eleanor; Oulton, Kate
Abstract : Background: Botulinum toxin-A (BoNT-A) is used in management of hypertonia in children and young people with cerebral palsy (CYPwCP). Evidence is limited regarding its effect on goal-directed outcome measures. Meaningful child-and-family-centred goal identification is an essential element of rehabilitation, ensuring interventions are targeted towards children's individual priorities. This prospective single site study assessed goal attainment in CYPwCP undergoing BoNT-A injections using the Canadian Occupational Performance Measure (COPM). Methods: Data were collected from 64 ambulant CYPwCP (Gross Motor Function Classification System levels I-III) aged 4 to 16 years undergoing lower limb BoNT-A injections within the movement disorder service at GOSH. Changes in COPM scores were analysed at 6-weeks, 6-months and 12-months post-intervention using Friedman tests. Participants' goals were classified according to the International Classification of Functioning, Disability and Health domains of Body Structure and Function, Activity and Participation and Environmental Factors. Results: COPM performance scores improved significantly from baseline to 6-weeks (median difference 3.17; p-value <0.001) and 6-months (median difference 2; p-value <0.001) and 12-months post-intervention (median difference 2.7; p-value <0.01). COPM satisfaction scores showed a similar pattern. Of 169 individual goals selected, 57.4% related to Activities and Participation, 37.3% related to Body Structures and Functions and 5.3% related to Environmental Factors. Activity and Participation goals demonstrated the most sustained positive response to BoNT-A injections over time. Conclusions: BoNT-A injections were associated with improved COPM scores at all post-injection time-points. The results suggested that goal achievement in Activity and Participation domains of the ICF showed more stability than those in Body-Structure-Function or Environment domains. Recommendations: Further longitudinal studies evaluating COPM scores are required, particularly those evaluating change with re-injection frequency and additional outcome measures. Detailed investigation of the responsiveness of goals throughout the domains of Activity and Participation would also help improve the accuracy of predicting response to BoNT- A injections.